2016
DOI: 10.1007/s12079-016-0332-z
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of CCN proteins in vascular development and pathology

Abstract: The CCN family of proteins consists of 6 members (CCN1-CCN6) that share conserved functional domains. These matricellular proteins interact with growth factors, extracellular matrix (ECM) proteins, cell surface integrins and other receptors to promote ECM-intracellular signaling. This signaling leads to propagation of a variety of cellular actions, including adhesion, invasion, migration and proliferation within several cell types, including epithelial, endothelial and smooth muscle cells. Though CCNs share si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…These proteins have been shown to be reservoirs of growth factors and to promote intracellular signaling. This occurs through the interaction with cell surface integrins, receptors, or other ECM molecules [232]. These molecules have been extensively studied and their role in the modulation of the proliferation, migration and adhesion of EC, among other cells, established.…”
Section: The Ccn Family Of Proteins As Regulators Of Vascular Devementioning
confidence: 99%
“…These proteins have been shown to be reservoirs of growth factors and to promote intracellular signaling. This occurs through the interaction with cell surface integrins, receptors, or other ECM molecules [232]. These molecules have been extensively studied and their role in the modulation of the proliferation, migration and adhesion of EC, among other cells, established.…”
Section: The Ccn Family Of Proteins As Regulators Of Vascular Devementioning
confidence: 99%
“…Ethical approval. All procedures followed were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national) and with the Helsinki Declaration of 1975, as revised in 2000 (5). Informed consent was obtained from all patients for being included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, vascular smooth muscle cells represent a distinct and terminally differentiated cell, and lack the multipotentiality of PSC. WISP-1 has also been implicated in the promotion of angiogenesis, especially in tumor associated angiogenesis 22 24 . In the current study, we found enrichment of WISP-1 within PSC both in situ , after purification, and after in vivo application in a bone defect microenvironment.…”
Section: Discussionmentioning
confidence: 99%